1972
DOI: 10.1103/physrevlett.29.324
|View full text |Cite
|
Sign up to set email alerts
|

Linear Stark Effect Due to Resonant Interactions of Static and Dynamic Fields

Abstract: In turbulent plasmas the radiating atoms are subjected to an oscillating high-frequency electric field originating from electronic plasma oscillations. It appears to be generally believed that in hydrogen plasmas the radiation spectrum in this situation is well described by the theory of the dynamical linear Stark effect developed by Blokhintsev. 1 However, the atoms are radiating also under the simultaneous influence of a quasistatic field due to slowly moving ions or to lowfrequency ion-acoustic turbulence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Cohn et al 5 , showed for Lya that resonant effects between high and low frequency fields can influence the intensity profile dramatically. This effect was found experimentally by Gallagher and Levine 6 and by Rutgers and DeKluiver 7 for the Balmer lines.…”
Section: Introductionmentioning
confidence: 99%
“…Cohn et al 5 , showed for Lya that resonant effects between high and low frequency fields can influence the intensity profile dramatically. This effect was found experimentally by Gallagher and Levine 6 and by Rutgers and DeKluiver 7 for the Balmer lines.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of position spectroscopy, as suggested here, offers-distinct advantages even for laboratory plasmas where other methods for the determination of field strengths are available. Hydrogenic spectra with discernible positions for various Stark shifted components of Balmer lines have already been observed in fusion related laboratory experiments with a high level of plasma oscillations (Gallagher and Levine, 1973).…”
Section: S -(~) Neaoesmentioning
confidence: 97%
“…The theory of the Stark effect for combined dynamic and static fields has been developed earlier by the authors Kalman, 1972, Bakshi, Kalman, andBakshi, Hogaboom, Kalman, and Cohn, 1974). A very brief sketch of this theory is given in Section 3, but first we can estimate the order of magnitude effects associated with the turbulent fields and their relation to Doppler broadening.…”
Section: Estimatesmentioning
confidence: 99%
“…[22] was pointed out in Ref. [17],where the L shell ( n = 2) has been considered numerically. Then in the framework of various approximations the time-dependent Schrodinger equation for n=2 (seldom for n=3, 4) was solved analytically [18 -21].…”
Section: Intrqductignmentioning
confidence: 99%